Parents' perceptions of provider communication regarding adolescent vaccines. Issue 6 (2nd June 2016) - Dempsey, Amanda F.; Pyrzanowski, Jennifer; Lockhart, Steven; Campagna, Elizabeth; Barnard, Juliana; O'Leary, Sean T.
ABSTRACT: Strong provider recommendations for adolescent vaccines are critical for achieving high vaccination levels. However, little is known about parents' preferred provider communication strategies for adolescent vaccines in general, and for human papillomavirus (HPV) vaccines specifically. We performed a cross-sectional survey of 800 parents of 9-14 year olds in April 2014 to assess current adolescent vaccine communication practices by providers, parents' preferred HPV vaccine-specific communication strategies, and the association of these two outcomes with experiential, attitudinal and demographic characteristics. Among the 356 parents in the study (response rate 48%), HPV vaccines were reported as less likely to have been "very strongly" recommended by their adolescent's provider (39%) than other adolescent-targeted vaccines (45%-59%, <0.05 for all comparisons). Receiving a very strong recommendation for HPV vaccines was associated with a higher likelihood of vaccine receipt (71% versus 39%, p<0.001), or among those not yet vaccinated, increased likelihood of positive vaccination intentions (82% vs. 60%, p = 0.015). Nearly all parents (87%) reported that, if available, they would use a website providing personalized HPV vaccine-related materials before their adolescent's next check-up, and other technology-based communications were also endorsed by the majority of parents. From these data we conclude that parents received weaker recommendations for HPV vaccines than other adolescent vaccines, and that most parents want additional HPV vaccine-related materials, preferably delivered using a variety of technology-based modalities which is not their providers' current practice.